Strategi Pengkaderan Partai Kebangkitan Bangsa (PKB) Di Pondok Pesantren Al Hidayah Wonoyoso Kabupaten Kebumen Tahun 2026 - Achmad Najib Amrullah; wahid Abdulrahman (Journal of Politic and Government Studies, 2026)
Cadre formation is crucial for a political party, as it is the core of the party's future struggle and the very essence of its existence. Partai Kebangkitan Bangsa (PKB) is an Islamic party with a well-established cadre formation pattern. PKB's political recruitment generally prioritizes candidates from Nahdlatul Ulama (NU) cadres who align with the party's ideology, one of which is cadre formation in Islamic boarding schools. The purpose of this study is to identify cadre formation strategies and analyze the impact of cadre formation in the Kebumen Regency PKB DPC on students at the Al Hidayah Wonoyoso Islamic Boarding School in Kebumen. This study uses a descriptive qualitative method, with purposive sampling used to determine research informants. Data collection uses observation, interviews, and documentation. Interviews were conducted with the Kebumen PKB DPC administrators, caretakers, students, and alumni of the Islamic boarding school. The results of the study indicate that the cadre development strategy of the DPC PKB Kebumen at the Al Hidayah Wonoyoso Islamic Boarding School culturally involves the leadership of the Islamic boarding school in the party structure or advisory board/syuro, involves students and alumni in various activities organized by the DPC PKB Kebumen, carries out political education through the instillation of political values formally and informally, talent scouting, and mentoring that focuses on unifying the traditional values of Islamic boarding schools with the needs of modern politics. The cadre development of the DPC PKB Kebumen at the Al Hidayah Wonoyoso Islamic Boarding School has a positive impact in the form of increasing literacy and political awareness of students, producing militant cadres, with integrity, and a national spirit, strengthening the relationship between Islamic boarding schools and national politics, and strengthening moderate ideology (wasathiyyah)